2020
DOI: 10.35816/jiskh.v12i2.364
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Isometric Handgrip Exercise dalam Menurunkan Tekanan Darah pada Pasien Hipertensi

Abstract: Abstract. Background: Hypertension has a significant impact on public health and has become a major health care burden worldwide. One non-pharmacological therapy that can be given to reduce blood pressure in hypertensive patients is Isometric Handgrip Exercise exercise therapy. This therapy has been shown to reduce blood pressure which is almost the same as intense aerobic exercise. This literature review aims to analyze the effects of the application of Isometric Handgrip Exercise in reducing blood pressure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
7
0
7
Order By: Relevance
“…The average decrease in systolic blood pressure and diastolic blood pressure in the intervention group was 7.48 ± 0.06 mmHg and 6.41 ± 1.01 mmHg, respectively, and significantly increased systolic blood pressure, diastolic and pulse rate in 5 minutes after exercise at 30% MVC with mean values of 8.60 ± 0.20 mmHg, 7.33 ± 0.03 mmHg, and 8.24 ± 0.20 beats/min. This is in line with the research of Zainuddin & Labdullah (2020) which showed that the Isometric Handgrip Exercise was proven to be effective in reducing blood pressure in hypertensive patients. In a study conducted by Sandhu et al, (2014) the results showed that the isometric handgrip exercise decreased resting heart rate and arterial pressure in normotensive individuals.…”
Section: Effect Of Isometric Handgrip Exercie On Blood Pressuresupporting
confidence: 90%
See 1 more Smart Citation
“…The average decrease in systolic blood pressure and diastolic blood pressure in the intervention group was 7.48 ± 0.06 mmHg and 6.41 ± 1.01 mmHg, respectively, and significantly increased systolic blood pressure, diastolic and pulse rate in 5 minutes after exercise at 30% MVC with mean values of 8.60 ± 0.20 mmHg, 7.33 ± 0.03 mmHg, and 8.24 ± 0.20 beats/min. This is in line with the research of Zainuddin & Labdullah (2020) which showed that the Isometric Handgrip Exercise was proven to be effective in reducing blood pressure in hypertensive patients. In a study conducted by Sandhu et al, (2014) the results showed that the isometric handgrip exercise decreased resting heart rate and arterial pressure in normotensive individuals.…”
Section: Effect Of Isometric Handgrip Exercie On Blood Pressuresupporting
confidence: 90%
“…The results of research conducted by Zainuddin & Labdullah (2020) show that several literature review articles show that the Isometric Handgrip Exercise is proven to be effective in reducing blood pressure in hypertensive patients. Handgrip isometric exercise can reduce cardiovascular reactivity to psychophysiological stressors in people suffering from hypertension (Badrov et al, 2013).…”
Section: Effect Of Isometric Handgrip Exercie On Blood Pressurementioning
confidence: 99%
“…Selanjutnya pada pengujian signfikansi parsial ditemukan bahwa nilai sig 0.01 < 0.05 sehingga dapat disimpulkan bahwa konseling berpengaruh positif dan signifikan terhadap kepatuhan (13).…”
Section: Pengujian Analisis Regresi Linear Sederhana Dan Pengujian Hi...unclassified
“…Berdasarkan hasil pengujian ditemukan bahwa mayoritas responden pada penelitian ini berusia 59-67 tahun yang berjumlah 24 orang atau 61.5%, selanjutnya terdapat 9 orang atau 23.1% yang berusia 68-76 tahun, 5 orang atau 12.8% yang berusia 50-58 tahun dan 1 orang atau 2.6% yang berusia lebih dari 76 tahun(13). Semakin tinggi umur seseorang atau semakin tua seseorang maka akan semakin tinggi terkena risiko hipertensi.…”
unclassified
“…Peningkatan otot yang terlatih dan peningkatan airan pembuluh darah akan mempertahankan kemampuan otot yang meningkat, mempertahankan metabolisme aerobic, membangkitkan respon simpatik yang lebih kecil sehingga tekanan darah lebih sedikit tidak meningkat. Saat latihan berlangsung, reflek komereseptor akan menurunkan aktivitas saraf simpatik sehingga melemahnya respon saraf simpatik akan berakibat penurunan tekanan darah istirahat (Zainuddin & Labdullah, 2020). Usia >18 tahun keatas yang mengalami tekanan darah tinggi dapat terjadi dari beberapa faktor.…”
Section: Tekanan Darah Setelah Diberikan Latihan Isometric Handgrip E...unclassified